Elucidation of mechanisms of antibiotic subversion in mycobacteria - Naran, Krupa (Division of Medical Biochemistry, 2015)
The intrinsic resistance of Mycobacterium tuberculosis ( Mtb ) to antibiotics is generally attributed to multiple factors, most significantly the low permeability of the mycobacterial cell wall, the operation of various drug inactivating systems, and the activity of efflux pumps. This study aimed to investigate the role of various components of the "intrinsic resistome" that limit the efficacy of antitubercular agents. The DNA damage response: the SOS response was hypothesized to play a role in antibiotic- mediated cellular death, and that disabling the mycobacterial SOS response, by generating non-cleavable LexA mutants (lexA Ind-), could be used as a tool to validate antibiotic-mediated cell death. To this end, the M. smegmatis (Msm) cleavable LexA was shown to be essential for induced mutagenesis and damage tolerance and that an intact DNA damage repair system is required to respond to antibiotic-mediated DNA damage. In contrast, Mtb cleavable LexA was required for induced mutagenesis but not necessarily damage sensitivity. In addition, the Mtb SOS response does not contribute significantly to remediation of antibiotic-mediated DNA damage. Collectively, these data suggest that DNA repair mechanisms differ between the mycobacterial species and despite effectively inactivating the LexA-dependent DNA repair mechanism(s) in Msm and Mtb, these organisms are able to circumvent this pathway and successfully remediate damaged DNA sustained under various conditions. Furthermore, Mtb auto-bioluminescent reporter strains were generated by introducing the lux operon downstream of the recA or radA promoters. Analysis of a panel of antimicrobials against these strains allowed for the identification of true DNA-damaging agents and the evaluation of the kinetics of the DNA-damage response, in a concentration- and time-dependent manner. Efflux-mediated drug resistance: This study aimed to evaluate the interactions between pairwise combinations of selected antimicrobials and efflux pump inhibitors (EPIs), in vitro and ex vivo, and to identify a novel verapamil (VER)-analogue with improved efficacy against Mtb. Subsequently, a candidate EPI was identified, with equivalent in vitro synergistic effects to VER when used in combination with various antibiotics but with reduced cytotoxic effects, ex vivo, when compared to VER. Mycothiol-mediated protection : It was hypothesized that undetectable levels of mycothiol ( MSH ) in Mtb would potentiate the use of current antibiotics. To investigate the contribution of the cellular antioxidant, MSH, to the mitigation of antimicrobial efficacy, this study aimed to disrupt MSH production by conditionally knocking-down expression of the essential gene, mshC. The mshC knock-down mutants (in all configurations) were not anhydrotetracycline (ATC)-regulatable in liquid or on solid medium, which was subsequently validate d with quantitative gene expression analysis. These data suggest that a tetracycline (Tet)-based conditional expression system may not be applicable to mshC. In conclusion, Mtb has a multitude of inherent mechanisms to subvert the effects of antimicrobial treatment. This study has contributed to the understanding of certain aspects of the intrinsic resistome and in doing so, established tools that can be used in future drug discovery programmes.